Evaluasi Kelayakan Pemberian Kredit Oleh PT BPR Artha Sari Kencana Malang - Prasetyo, Irawan Budi (Fakultas Ekonomi Universitas Wisnuwardhana, 2018)
Abstraction. Credit Evaluation is an important element in lending to debtors. Crediting activities required a good and thorough analysis of all aspects of credit that can support the crediting process, in order to prevent the emergence of a credit risk. The purpose of this study is to determine the feasibility of giving credit made by the PT BPR Artha Sari Kencana Malang. From the result of data analysis using 6C analysis tool that is character, capacity, capital, collateral, condition and compliance stated that most of the debtor deserve credit from PT BPR Artha Sari Kencana Malang. Based on the 6C analysis tool, it was found that eligible credit received 80% (as many as 12 people), while unacceptable credit received 20% (as many as 3 people). Keyword: evaluation, credit